GP284 The effects of ivacaftor on pancreatic function in paediatric patients with cystic fibrosis gating mutations. (June 2019) - Emery, Joshua; Mullane, David; Chroinin, Muireann Ni
Abstract : Objectives: To examine the effects of Ivacaftor on growth and pancreatic function in patients attending the Paediatric Cystic fibrosis (CF) Centre at Cork University Hospital. Methods: A retrospective, convenience sampled cohort analysis was conducted in patients aged 2 to 17 with genetically confirmed CF (N=28, 15 male, 13 female). Subjects who received Ivacaftor over a 1 year period had an oral dose of either 75 or 150 mg twice daily depending on weight. Patients were excluded if concurrently taking Lumacaftor. The primary end points were estimated mean change from baseline through one year in pancrealipase (Creon) consumption per day and body mass index (BMI). Secondary end points included the changes in mean percent of predicted forced expiratory volume in 1 second (FEV1 ) as well as exocrine pancreatic marker faecal elastase-1 (FE-1) and random blood glucose within the Ivacaftor group. Results: The change in pancrealipase use was significantly decreased in the Ivacaftor group in comparison to controls (1202± 587 IU/kg, p=0.039). In addition, Ivacaftor users had a significant increase in gross BMI (0.98± 0.51 kg/m 2, p=0.010) and a non-significant increase in FEV1 % predicted (10.9± 5.06%, p=0.123) in comparison to controls. On subgroup analysis, there was significant improvement in FE-1 after one year of Ivacaftor use (107± 80.8μg/g, p= 0.013, N=7). As well, there was mild decrease seen in random blood glucose, however this result was not significant (-0.43± 0.87 mmol/L, p=0.153, N=10). Conclusions: Ivacaftor improves paediatric CF patients' BMI, blood glucose, and FE-1 values while reducing their reliance on pancrealipase. This data supports previous research showing increasing lung function in Ivacaftor users. Subgroup analysis of those with serial FE-1 results revealed that 43% of those taking Ivacaftor reached pancreatic exocrine sufficiency (FE-1> 200μg/g). This implies that further study of Ivacaftor's pancreatic implications is warranted. Similarly, prospective studies of new and emerging drugs of this class in a similar manner could yield positive results for patients.